2000
DOI: 10.1161/01.str.31.2.448
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Risk Model for Outcomes of Ischemic Stroke

Abstract: Background and Purpose-The great variability of outcome seen in stroke patients has led to an interest in identifying predictors of outcome. The combination of clinical and imaging variables as predictors of stroke outcome in a multivariable risk adjustment model may be more powerful than either alone. The purpose of this study was to determine the multivariable relationship between infarct volume, 6 clinical variables, and 3-month outcomes in ischemic stroke patients. Methods-Included in the study were 256 el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(171 citation statements)
references
References 49 publications
7
157
0
7
Order By: Relevance
“…45,69 Some studies used Ͼ1 ADL measurement in their prognostic investigations. 23,42,61 The Barthel Index (BI; Kϭ24) 23,24,26,29,31,32,34,37,41,42,45,46,51-53,58 -62,64 -66,68 was the most frequently used scale to assess ADL outcome, followed by the modified Rankin scale (Kϭ18), 21-23,25,30,35,37,38,42,44, …”
Section: Study Characteristicsmentioning
confidence: 99%
“…45,69 Some studies used Ͼ1 ADL measurement in their prognostic investigations. 23,42,61 The Barthel Index (BI; Kϭ24) 23,24,26,29,31,32,34,37,41,42,45,46,51-53,58 -62,64 -66,68 was the most frequently used scale to assess ADL outcome, followed by the modified Rankin scale (Kϭ18), 21-23,25,30,35,37,38,42,44, …”
Section: Study Characteristicsmentioning
confidence: 99%
“…The sample size was large (larger than the sum total of all 17 previous studies identified in systematic review), 4 includes patients admitted with acute stroke to all hospitals in England and Wales, and reflects the outcomes of contemporary stroke care. Many of the previously developed models were based on data from single sites 22 or interventional cohorts, 6,23 or were derived from historic cohorts 24 of patients who had stroke at a time before the widespread use of interventions proven to improve outcomes after stroke, such as organized stroke unit care. 25 The validity of these models in predicting the outcomes of contemporary patients with stroke is therefore uncertain.…”
Section: Strokementioning
confidence: 99%
“…Various studies have concluded that it is predictive of stroke outcomes. [16][17][18] One study demonstrated that severity of stroke assessed by NIHSS at admission to be predictive of 3 month mortality and another study established it as an independent predictor of 30 days mortality.…”
Section: Discussionmentioning
confidence: 99%